Improving the nutritional and livelihood security of landless laborer through the Backyard Farming System - Sahoo, Lopamudra; Kandpal, Basant Kumar; Das, Anup; Debnath, Chandan; Singh, Vinay; Devi, Hiangmayum Lembisana; Bharati, Huirem; Parhi, Janmejay; Singha, Abhijit; Datta, Joydeep; Das, Biswajit; Mishra, Vinay Kumar (Frontiers in Sustainable Food Systems, 2023)
India is home to around 140 million landless labourers who come below poverty line and are the most vulnerable group in terms of food and nutritional security. The three critical problems faced by the poor labourer family are poverty, hunger and malnutrition.To address these problems, a backyard farming system was conceptualized and evaluated with an aim to ensure nutritional security of landless labourers. The main objective of this work was to utilize the homestead area of 100-150m2 for ensuring year round food availability for the family. Integration of vegetables, pulses, fruits, spices, fishes and ducks were done in the limited available area. Technological interventions with the integration of ducks (Khaki campbell),fish (carps and Self recruiting species),pulses, leafy vegetables, can help in improving the nutrient consumption of the family. A total of 1400 kg of vegetables (including root vegetables and leafy vegetables) could be produced annually from an area of 150m2 that can fulfil 30-70% of the vitamins (RDA of 70 % of B1 and 30% of B3) and mineral requirements (RDA of 45% of Iron and 30% of Ca) of the family, besides an annual saving of INR 25,000/annum and an extra income of INR 10,000/annum that can be earned from selling of the extra produce. Herbs (Coriander, Mint, Fenugreek) and spices (Ginger, Turmeric, Chilli) with antioxidants ranging from 2-13 millimol/100gm can help in developing a good immune status for the family. Integration with ducks, pond dyke utilization with cucurbits, spices and herbs and introduction of self-recruiting species in composite fish culture system can further enhance the income by INR 14,000/annum after family consumption. Year round cultivation was done thereby making the optimum use of the available resources. A net return of INR. 30,000 from 300 m2 could be obtained with B:C ratio of 2.98 besides generating an employment of 136 mandays. The food produced from the system can contribute to the nutritive requirements throughout the year besides leading to a greater diversity in the food consumption pattern of the family.